Uji Aktivitas Antibakteri Formulasi Gel Ekstrak Daun Kelor (Moringa oleifera) terhadap Staphylococcus aureus - Astara Ginarana; Efrida Warganegara; Oktafany (MAJORITY, 2020)
Staphylococcus aureus is one of the bacteria that is pathogenic to humans and is most often transmitted from hand to hand. Moringa leaf gel as an alternative as an antibacterial. The purpose of this research is to determine the antibacterial activity of Moringa oleifera leaf extract in gel formulation against Staphylococcus aureus. This type of research is an experimental laboratory with the method of sump on Mueller Hinton Agar media. Moringa oleifera leaf extract was obtained from the Organic Chemistry Laboratory of the University of Lampung with maceration techniques using 96% ethanol. Gel formulations were made at Cendikia Farma Husada Pharmacy Vocational School Bandar Lampung. Moringa oleifera leaf extract is divided into several concentrations namely 5%, 10%, 20%, 40% and 80%. As a negative control, distilled water gel and positive control were erythromycin (Erymed®) gel. The data obtained is based on the results of the measurement of the inhibition zone formed around the sump and measured by the calipers. Data were tested by One Way ANOVA. The results of this study indicate that the diameter of the inhibitory zone formed in the Moringa oleifera leaf extract in gel formulation in concentration of 5%, 10%, 20%, 40% and 80%. Sequentially, namely 5.85 mm, 10.00 mm, 11.00 mm, 15.40 mm and 21.05 mm. In the negative control group it was 0 mm and positive control was 32.20 mm (p value = 0,000). There is an antibacterial activity of Moringa oleifera extract in gel formulation against Staphylococcus aureus.